Development of Flip PDF Professional Based Flipbook Learning Media on Basic Practical Elements of Hair Beauty for Class X Beauty Students of Gelora Jaya Nusantara Vocational School Medan - Nurhayati Tanjung; Dian Maya Sari; Anastasya Sabatinit (Universitas Muhammadiyah Enrekang, 2024)
This study aims to develop Flipbook learning media based on Flip PDF Professional and determine the feasibility of learning media on basic practical elements of hair beauty at SMK Gelora Jaya Nusantara Medan. The research method used in the Research & Development (R&D) research method with the ADDIE development model. The sample of this study was class X students of Beauty Management at SMK Gelora Jaya Nusantara Medan as many as 35 students. The research instrument used is a questionnaire instrument with descriptive statistical data analysis techniques. Based on the results of the research that has been done, the validation results from material experts get a score of 85.9% in the